2013
DOI: 10.1118/1.4829522
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐specific quantification of respiratory motion‐induced dose uncertainty for step‐and‐shoot IMRT of lung cancer

Abstract: Respiratory motion-induced dose uncertainty varies from patient to patient. Therefore, it is important to evaluate the dose uncertainty on a patient-specific basis, which could be useful for plan evaluation and treatment strategy determination for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Dosimetric effects of respiratory motion in lung cancers has been extensively studied, [19][20][21] however, we were unable to locate published articles for the stomach. In this report, we present the respiratory motion of the stomach and its impact on dosimetric parameters in IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…Dosimetric effects of respiratory motion in lung cancers has been extensively studied, [19][20][21] however, we were unable to locate published articles for the stomach. In this report, we present the respiratory motion of the stomach and its impact on dosimetric parameters in IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainties in the relationship between planned and delivered dose also include the interplay effect when using IMRT or VMAT as the delivery technique. These uncertainties seem to be small but, in some cases, may not be negligible . Several methods have been recently developed in an attempt to assess this effect …”
Section: Introductionmentioning
confidence: 99%
“…Li et al reported that the maximum point dose error due to respiration in intensity-modulated RT (IMRT) was estimated to be up to 6.2% based on RT plans, assuming a patient breathing cycle of 8 seconds (11). In our results, for IM, dose errors due to respiration in 3D-CRT were 2.8% and 6.2% for R05 and R10, respectively, while those in VMAT were slightly larger, 4.9% and 8.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%